2023
DOI: 10.1002/ldr.4814
|View full text |Cite
|
Sign up to set email alerts
|

Copper and cadmium content in Polish soil: Analysis of 25‐year monitoring study

Abstract: Metals can accumulate in agricultural soils, presenting a serious threat to human health; therefore, it is important to analyze the quality of these soils to avoid possible harm related to their contamination in the future. Despite the importance of monitoring arable soil quality, few studies have examined the current state of Cu and Cd soil contamination through analysis of historical data and temporal trends in heavy metal content. Therefore, this study was aimed at analyzing the spatial variability of Cu an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The geoaccumulation index (Igeo) is useful for assessing and analysing trace elements in soil as it intuitively reflects the impact of human activities on trace elements as well as the impact of trace elements on the environment [21,22]. The method was introduced by Muller [23] and is commonly used to quantify metal pollution in soils and aquatic sediments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geoaccumulation index (Igeo) is useful for assessing and analysing trace elements in soil as it intuitively reflects the impact of human activities on trace elements as well as the impact of trace elements on the environment [21,22]. The method was introduced by Muller [23] and is commonly used to quantify metal pollution in soils and aquatic sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The method was introduced by Muller [23] and is commonly used to quantify metal pollution in soils and aquatic sediments. Wdowczyk et al [22] found increased Cd levels in areas where intensive mining as well as metallurgical and industrial activities were carried out. Their study also indicates the impact of human activities on heavy metal concentrations in soils.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, soil contamination is often observed in industrialised areas, in metal ore mining and processing areas, near metallurgical and smelting plants, and land used for transport and agriculture [6,7]. A Polish study by Wdowczyk et al [8] found the mean Cd concentration in soil to increase from 0.7 to 3.4 mg/kg between 1995 and 2020. It is also important to note that while Cd is immobilised in soils with neutral and alkaline pH, it changes to a mobile form as the pH decreases [9].…”
Section: Introductionmentioning
confidence: 99%